Literature Review: Exercise for Patients with Type 2 Diabetes Mellitus Era Society 5.0 - Elsa Ariestika; Doni Pranata; I Putu Agus Dharma Hita; Satria Armanjaya (Jurnal Pendidikan Jasmani (JPJ), 2022)
Diabetes mellitus is one of the comorbid factors for respiratory infections due to Era Society 5.0. High blood sugar levels cause disturbances in the immune system, thereby exacerbating the infection. This study aims to discuss safe exercise for people with type 2 diabetes mellitus. This research is a type of literature study. The data collected was compiled using the literature study method. The approach used is analytic observational. Search articles using the Google Scholar search site with the keywords sports, diabetes mellitus, and Era Society 5.0. The results in this study are the recommended exercise for people with diabetes mellitus is light to moderate intensity exercise. It is necessary to consult with a doctor first regarding exercise options. Exercise at home is more recommended. As much as possible, physical activity should still be done by people with diabetes mellitus to stabilize blood sugar levels and improve the immune system. The conclusion of this study is that exercise in people with diabetes mellitus is very necessary during a pandemic. The exercise carried out must still comply with health protocols and in accordance with the condition of each individual's body.